PERFORMANCE STUDY OF COAL HAULING AND LOADING FROM PIT TO CPP AT CH PIT OF BINUNGAN SITE PT BERAU COAL - Maolana, Bayu
Coal loading and hauling are important activities in coal production chain. In the case of Binungan Mine Site - PT Berau Coal, coal loading and hauling are carried out from mining production front to Coal Processing Plant (CPP) with the hauling distance approximately 30 Km. The combination of loader and hauler used by PT Berau Coal is Komatsu PC-300 backhoe and 30 tons of Scania dumptruck. Considering that hauling distance, the performance of loader and hauler is one of the determining factors to achieve production target. This research is carried out to evaluate the performance of loading and hauling equipment in order to achieve production targets by considering the distance of coal hauling to CPP. In this research, the data of cycle time of Komatsu PC-300 and hauling time of dumptruck in weight-bridge of CPP are taken from field study. In addition, there are some supporting data such as; hauling distance data from the mining front to CPP, the average daily target of the CH Pit, and effective working hours. Furthermore, all the data and assumptions will be evaluated to determine the total number equipment for coal loading and hauling along with the relevant match factor. The result show that the required equipment to reach coal production target of 3500 tons coal per day are 18 units of 30 tons of Scania dumptruck and 1 unit of Komatsu PC-300. The increasing of hauling distance to 30 Km will require 35 units of 30 tons of Scania dumptruck and 1 units of Komatsu PC-300. In the case of increasing production target to 5200 ton per day with the average hauling distance around 28 Km will require 26 units of 30 tons of Scania dumptruck and 1 units of Komatsu PC-300. Furthermore, to achieve production target of 3500 ton per day could be carried out by modifying working shift from 3 shift to 2 shift per day. By modifying the working shift, it will require 16 units of 30 tons of Scania dumptruck and 1 units of Komatsu PC-300.